2016
DOI: 10.17061/phrp2611605
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing reductions in smoking among Australian adolescents

Abstract: A continued increase in the proportion of adolescents who never smoke, as well as an understanding of factors that influence reductions in smoking among this susceptible population, is crucial. The World Health Organization Framework Convention on Tobacco Control provides an appropriate structure to briefly examine Australian and New South Wales policies and programs that are influencing reductions in smoking among adolescents in Australia.This paper provides an overview of price and recent tax measures to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…One potential explanation for this could be the perceived images of these products among young people. The tobacco studies that found non-smokers were more likely to have reported seeing digital tobacco marketing were both conducted in Australia, where strong public health controls for tobacco products may have created unappealing images for these products [ 53 , 54 ] and people who disliked these products (non-smokers) might have paid more attention to the advertisements than current smokers. On the other hand, alcohol brands were marketed using themes of success, fun, masculinity and femininity; these were the images desired by and reported to be socially acceptable among young people to be seen with alcohol products on the SNS [ 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for this could be the perceived images of these products among young people. The tobacco studies that found non-smokers were more likely to have reported seeing digital tobacco marketing were both conducted in Australia, where strong public health controls for tobacco products may have created unappealing images for these products [ 53 , 54 ] and people who disliked these products (non-smokers) might have paid more attention to the advertisements than current smokers. On the other hand, alcohol brands were marketed using themes of success, fun, masculinity and femininity; these were the images desired by and reported to be socially acceptable among young people to be seen with alcohol products on the SNS [ 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking prevalence among European adolescents is higher than in other parts of the world, such as Australia and North America. 1,2 In 2013, around 10% of European adolescents aged 15-17 years were daily or current smokers, according to self-reported data. 3,4 At least one-fourth of the adolescent smoking population continues smoking at later age, 5,6 which may be driven by high levels of nicotine dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Future research could examine whether the benefits following introduction of smoke-free outdoor policies support extending these spaces to include vaping and what the impact on ENDS users would be. Smoke-free outdoor policies are associated with reductions in youth smoking initiation 39 40. Vape-free areas could reduce exposure to ENDS and decrease perceptions of vaping as ‘normal’.…”
Section: Discussionmentioning
confidence: 99%